2020
DOI: 10.3390/agronomy10010115
|View full text |Cite
|
Sign up to set email alerts
|

Salicylic Acid and Putrescine to Reduce Post-Harvest Storage Problems and Maintain Quality of Murcott Mandarin Fruit

Abstract: Natural products have been used to improve citrus fruit quality and storability, which increase the fruit marketing period and exportation to distant markets. This study was conducted to evaluate the role of salicylic acid and putrescine on reducing post-harvest loss and maintaining the quality of stored Murcott mandarin. Fruit were harvested at 297–300 days from full bloom, and five 5-min dipping treatments were applied; salicylic acid (200 and 400 ppm), putrescine (50 and 100 ppm), and the control. One group… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(23 citation statements)
references
References 55 publications
(52 reference statements)
1
20
0
2
Order By: Relevance
“…The participation of SA in systemic gained resistance has also been stated by Beckers and Spoel (2006). There are many studies suggesting beneficial impacts of SA treatment of preserving fruit quality and reducing decay percentage (Ennab et al, 2020;Gonchikari et al, 2020 andHaider et al, 2020).…”
Section: Qualitative Traitsmentioning
confidence: 94%
“…The participation of SA in systemic gained resistance has also been stated by Beckers and Spoel (2006). There are many studies suggesting beneficial impacts of SA treatment of preserving fruit quality and reducing decay percentage (Ennab et al, 2020;Gonchikari et al, 2020 andHaider et al, 2020).…”
Section: Qualitative Traitsmentioning
confidence: 94%
“…Salicylic acid (SA), chemically known as two hydroxy benzoic acid is one of a diverse group of phenolic compounds. Studies have demonstrated that SA acts as a signaling molecule; regulates respiration, senescence‐associated gene expression, and enzymatic activities; controls diseases and extend the storage life of fruits 6–9 . SA also exhibits antagonistic effects on both ethylene biosynthesis and ethylene action 10 .…”
Section: Introductionmentioning
confidence: 99%
“…Recently, researchers have shown an interest in the application of nontoxic alternatives or supplements to synthetic fungicides. Plant extracts, including essential oils, have been investigated as alternative measures against pathological breakdown (Klieber et al, 2002;Ahmed et al, 2007;Badawy-Ibtesam et al, 2011;Zaghloul et al, 2011 andBarakat et al, 2015 Coating fruit has been associated with protect perishables from deterioration by reducing transpiration and respiration, improving textural quality, retaing colour and volatile flavour compounds and reducing microbial growth (Mahmoud-Thanaa et al2017, Bakhtiarizade and souril, 2019, Taslima et al 2020and Ennab et al 2020 Thus, the main goal of this study was to investigate the effect of -dipping balady mandarin fruits with camphor oil, linen oil either as single treatment or combined with Imazalil as a chemical fungicide on postharvest fruits quality attributes during cold storage for 4 monthes.…”
Section: Introductionmentioning
confidence: 99%